A Hexanuclear Cobalt(II) Cluster Incorporated in a Banana‐Shaped Tungstovanadate: [(Co(OH2)Co2VW9O34)2(VW6O26)]17–. Issue 10 (19th December 2012) - Lv, Hongjin; Song, Jie; Geletii, Yurii V.; Guo, Weiwei; Bacsa, John; Hill, Craig L.
Abstract: The hexanuclear cobalt‐containing tungstovanadate complex, Na17 [(Co(OH2 )Co2 VW9 O34 )2 (VW6 O26 )]· 31H2 O (1 ) has been synthesized through reaction of cobalt nitrate, sodium tungstate, and V2 O5 in acetate buffer solution. The title compound has been characterized by X‐ray crystallography, elemental analysis, FTIR, UV/Vis, and 51 V NMR spectroscopy and by cyclic voltammetry. Complex1 crystallizes in the monoclinic space group P 21 / c ( a = 15.706(3) Å, b = 21.973(5) Å, c = 35.080(8) Å, α = 90°, β = 97.420(3)°, γ = 90°; V = 12005(5) Å 3 ; Z = 4; based on 192337 independent reflections), which consists of two tri‐Co II substituted B‐α‐[(Co(OH2 )Co2 VW9 O39 )] Keggin units bridged by one unique [VW6 O16 ] fragment leading to a banana‐shaped structure with idealized C 2 ν symmetry. Stability studies show that polyoxoanion1 ultimately transforms into the tetracobalt‐containing sandwich‐type polyoxoanion, 2, as confirmed by 51 V NMR and X‐ray crystallographic analyses. Polyoxoanion1 shows catalytic activity for the H2 O2 ‐based epoxidation of 1‐hexene and cyclohexene in 1, 2‐dichloroethane solvent. Abstract : The hexacobalt tungstovanadate, Na17 [(Co(OH2 )Co2 VW9 O34 )2 (VW6 O26 )]· 31H2 O (1 ), has been prepared and characterized both in the solid state and in solution. It crystallizes in the monoclinic space group P 21 / c, and consists of two tri‐Co II substituted B‐α‐[(Co(OH2 )Co2 VW9 O39 )] Keggin units bridged by one unique [VW6 O16 ] fragment, leading to a banana‐shaped structure with idealized C 2 ν symmetry.